CHARACTER DEVELOPMENT IN THE SELFISH GIANT BY OSCAR WILDE: A TRANSITIVITY ANALYSIS - Adib Muhammad, Alifya Shaumi (Fakultas Ilmu Budaya, Universitas Padjadjaran, 2026)
Character development in children’s literature is frequently manifested through moral crises that demand shifts in a character’s internal perspective. This study aims to analyze the evolution of the Giant’s transitivity patterns in Oscar Wilde’s The Selfish Giant to reveal his moral transformation. Applying Halliday’s Systemic Functional Linguistics, the research examines process types, participants, and circumstances across two narrative stages. The results reveal a significant shift from dominant material processes representing physical control and isolation to an increase in mental and relational processes. This shift signifies a transition in the character’s mental state from selfish stagnation and moral unconsciousness to empathetic awareness and social connectedness. Furthermore, dominant spatial circumstances illustrate the narrative’s movement from isolation to renewal, proving that linguistic choices systematically construct character development and reinforce the story’s central themes.